Revision of parasitoids of Massicus raddei (Blessig & Solsky) (Coleoptera, Cerambycidae) in China, with one new species and genus - Cao, Liang-Ming; Achterberg, Cornelis Van; Tang, Yan-Long; Wang, Xiao-Yi; Yang, Zhong-Qi (Zootaxa, 2020)
Fifteen parasitoids of Massicus raddei (Blessig & Solsky) (Coleoptera, Cerambycidae) are revised. The host is a serious pest of Quercus liaotungensis Koidz. and Q. mongolica Fisch. ex Ledeb. in NE China. All the parasitoids were reared from larvae of M. raddei. Pseudocyanopterus gen. nov. raddeivorus sp. nov., a new braconid wasp is described, and Cyanopterus tricolor (Ivanov) and Eubazus (E.) pallipes are new records for the Chinese fauna. An identification key to the parasitoids of M. raddei in China is provided. Detailed photographs of the parasitoids are provided.